Economic policy coordination in the EMU: From Maastricht via SGP to the fiscal pact - Jørgen Mortensen (Center for Social and Economic Research (CASE), 2013)
The present paper first takes a step backwards with an attempt to situate the adoption of this Treaty in discussion of the SGP and the "Maastricht criteria" (the criteria for EMU membership fixed in the Maastricht Treaty) in a longer perspective of the sharing of competences for macroeconomic policy making within the EU from the initial Treaty to the Maastricht Treaty and the Stability and Growth Pact (SGP). It then presents the main features of the Fiscal Treaty and its relation to the SGP and draws some conclusions as regards the importance and relevance of this new step in the process of economic policy coordination. It concludes that the Treaty on Stability, Coordination and Governance in the Economic and Monetary Union does not seem to offer a definitive solution to the problem of finding the appropriate budgetary-monetary policy mix in the EMU already well identified in the Delors report in 1989 and regularly emphasised ever since and now seriously aggravated due to the Crisis. Furthermore, the implementation of this Treaty may under certain circumstances contribute to an increase in the uncertainties as regards the distribution of the competences between the European Parliament and national parliaments and between the former and the Commission and the Council.
Keywords: E61; E62; E52; 330; Economic Policy Coordination; Stability and Growth Pact; Maastricht Treaty; Fiscal Treaty; Sustainability of Fiscal Policy